2007
DOI: 10.1080/00365590701303702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anxiety between patients with mixed incontinence and those with stress urinary incontinence

Abstract: This study provides objective evidence that patients with MI have a higher degree of anxiety than those with pure SUI. Therefore, we suggest that doctors should pay more attention to anxiety symptoms when caring for patients with MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Anxiety has been previously associated with a many types of incontinence (stress, mixed, urge) and LUTS. 25 In this study we found an association between high anxiety and LUTS. It is not clear whether women with anxiety simply are more likely to report LUTS, whether LUTS causes more anxiety, or whether anxiety somehow worsens LUTS.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Anxiety has been previously associated with a many types of incontinence (stress, mixed, urge) and LUTS. 25 In this study we found an association between high anxiety and LUTS. It is not clear whether women with anxiety simply are more likely to report LUTS, whether LUTS causes more anxiety, or whether anxiety somehow worsens LUTS.…”
Section: Discussionsupporting
confidence: 51%
“…These findings are consistent with those reported in previous studies. 25-26 Dwyer et al 26 has reported that obesity was significantly more common in women with stress and urge incontinence. The excess weight in these individuals has been thought to create excess strain on the pelvic floor muscles and nerves resulting in these urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzed the association between urinary incontinence and anxiety symptoms. Lim et al 25 investigated anxiety symptoms between women with SUI and with mixed urinary incontinence and found that women with MUI had more anxiety when compared to women with just SUI. The authors emphasized the importance of the approach used when treating anxiety symptoms in patients with MUI.…”
Section: Discussionmentioning
confidence: 99%
“…3 These findings were consistent with other studies demonstrating higher anxiety and depression rates among patients with UI. 29, 30 The direction of the relationship(s) between UI and mental health are as yet unknown and may be bidirectional. Additional research is warranted to further define these relationships and potentially exploit novel opportunities for intervention.…”
Section: Discussionmentioning
confidence: 99%